Estimating the inhibitory effect of Lactobacillus isolated from vagina against some pathogens of genital infections in group of women. - S. Hindal, Azhar .; A. Ali, Sameer . (Iraqi Journal of Science, 2023)
Thirty- five vaginal swab samples were obtained from women vagina.All sampleswere subjected to conventional morphological and cultural characteristics, isolatesdistributed between Lactobacillus acidophillus(23)and Lactobacillus fermentum (12).Antibacterial activities were done by well diffusion and blank disk method. TheLactobacillus was used as aprobiotic treatment against bacteriaisolates from vagina.The isolated bacteria had strong activity against indicator strains.The results showedthat Lactobacillus which was isolated from vagina by well diffusion method waseffective against pathogenic isolates more than the Lactobacillus isolated by blankdisc method , the highs inhibitory effect of Lactobacillus isolates by well give aninhibition zone reached to(18)mm , while the Lactobacillus by disc was lower withinhibition zone (12-15) mm. Also the results revealed that Lactobacillus spp. wholecell of Lactobacillus was more effective against pathogenic isolates more thanusedsupernatant . The supernatant did not show any activity when was treated withNaOH and adjusted to pH 7. This indicates that the organic acid produced by theLactobacillus isolates was may be actually responsible for the inhibition of theindicator bacteria.The result show that theLactobacillus strains could be consideredasapotential antimicrobial probiotic strains against some human vaginal pathogensand should be further studied for their human health benefits.